Delayed Marriages in Pakistan (The Pakistan Development Review, 1986)
Delayed marriages played a very important role in slowing down population growth during the European Demographic Transition. Similarly, some developing countries have recently undergone even more rapid changes in marriage patterns, leading to declining levels of fertility. Curtailing marriage or entry into sexual unions is one of the "positive" checks posited by Malthusian theory and is worthy of some renewed attention because of the lack of decline in marital fertility in Pakistan. Several researchers have identified changes in nuptiality behaviour in Pakistan, in terms of a rise in both the average age at marriage [8; 11; 12] and changes in cohort nuptiality [7]. One researcher observed a slight decline in fertility and attributed it to a rise in the age at marriage in the late Seventies [1], but his observation was found to be an artefact of data and was, therefore, refuted (18] . Thus, nuptiality behaviour has been noted to have changed in Pakistan since the Fifties with no notable accompanying changes in marital fertility. This paper's primary objective is to explore the impact of modernization, particularly of expansion of education and modern sector employment, urbanization and migration, on proportions never married in various age groups.